The early design stage of a novel Solar Thermal Façade (STF) for building integration: energy performance simulation and socio-economic analysis - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Wu, Yupeng; Pan, Song; Wu, Jinshun; Xu, Peng (Elsevier, 2016)
This paper provides a feasibility study of a new solar thermal façade (STF) concept for building integration from both technical and economic aspects in Shanghai area of China. The whole set of technical evaluation and economic analysis was investigated through simulation of a reference DOE residential building model in IES-VE software and a dedicated dynamic business model consisting of several critical financial indexes. In order to figure out the cost effectiveness of the STF concept, research work consisted of: (1) exploring the overall feasibility, i.e. energy load, energy savings, operational cost and environmental benefits, and (2) investigating the financial outputs for investment decisions within three different purchase methods. This paper presents a multidisciplinary research method that is expected to be beneficial and supportive for the strategic decision at the early design stage and it also offers a different angle to assess the economic performance of the STF application.